Penerapan Algoritma C4.5 untuk Pehamanan Siswa SMK Pada Pelajaran Kompetensi Keahlian - Sofia Dewi; Oktaviawati Oktaviawati (Masoem University, 2022)
Understanding the process of teaching and learning activities is very important, because these activities can produce high achieving students if the process occurs successfully. This study aims to carry out the classification process using the C4.5 Algorithm on the concept of the level of understanding of students in the Basic Network Computer skills subject so that it can be used as a reference for improving student achievement and making benchmarks for learning media that must be improved and teachers as one of the important indicators in during the learning process. This study uses data based on a questionnaire. The data obtained is 136 data and divided into 100 training data data and 36 data for testing data. The results of the implementation of the classification process using the C4.5 Algorithm for students' interest in understanding the competency skills subject at Guna Dharma Nusantara Vocational School produce an indicator of learning media that has the highest gain so that it makes an important indicator of the student's interest in understanding. The application used for testing the classification process is RapidMiner with an accuracy value of 97.22%.